Leishmaniasis patients' pilgrimage to access health care in rural Bolivia: a qualitative study using human rights to health approach - Daniel Eid; Miguel San Sebastian; Anna-Karin Hurtig; Isabel Goicolea (BMC, 2019)
Abstract Background Leishmaniasis is a neglected tropical disease endemic in Bolivia that disproportionately affects people with little social and political capital. Although the treatment is provided free of charge by the Bolivian government, there is an under-utilization of treatments in relation to the estimated affected population. This study explores the experiences of patients with leishmaniasis and the challenges faced when searching for diagnosis and treatment in Bolivia using a human rights approach. Methods We conducted open-ended interviews with 14 participants diagnosed with leishmaniasis. The qualitative data were analysed using thematic analysis and were interpreted under a human rights approach to health care. Results Four themes emerged during data analysis: (1) the decision for seeking a cure takes time; (2) the severity of symptoms and disruption of functioning drives the search for Western medicine; (3) the therapeutic journey between Western and traditional medicine; and (4) accessibility barriers to receive adequate medical treatment. This study showed that access to health care limitations were the most important factors that prevented patients from receiving timely diagnosis and treatment. Cultural factors played a secondary role in their decision to seek medical care. Conclusions Accessibility barriers resulted in a large pilgrimage between public health care and traditional medicinal treatments for patients with leishmaniasis. This pilgrimage and the related costs are important factors that determine the decision to seek health care. This study contributes to the understanding of the under-utilisation problems of medical services in leishmaniasis and other similar diseases in remote and poor populations.